Primary synovial sarcoma of the thyroid gland: a CARE compliant case report and literature review - Ren, Chutong; Li, Yashan; Huang, Jiangsheng; Liu, Sushun; Cao, Zhexu; Jiang, Qin; Lin, Xiang; Ye, Fei; Gong, Yi (Frontiers in Medicine, 2023)
Rationale Synovial sarcoma is a subtype of soft tissue sarcoma. Synovial sarcoma in the head and neck region is relatively unusual. Primary synovial sarcoma of the thyroid gland (PSST) is first reported in 2003 by Inako Kikuchi. PSST is extremely rare with only 15 cases documented globally. PSST shows rapid disease progression and a relatively poor prognosis. However, diagnosis and therapy are challenging for clinical surgeons. In this article, we reported the 16th PSST case and reviewed the PSST cases globally for further clinical application. Patient concerns The patient was referred to us because of gradually worsened dyspnea and dysphagia for 20 days. Physical examination showed a 5 × 4 cm mass with a clear boundary and good mobility. Contrast-enhanced ultrasonography (CEUS) and computed tomography (CT) showed a mass in the isthmus of the thyroid gland. The imageology diagnosis tends to be a benign thyroid nodule. Diagnosis After surgery, histopathology, immunohistochemistry, and fluorescence, in situ hybridization indicated the mass to be primary synovial sarcoma of the thyroid gland with no local and distant metastasis. Interventions The patient underwent total thyroidectomy and dissected the lymph nodes in the central compartment. This patient received postoperative chemotherapy (a combination of ifosfamide and epirubicin for five cycles). Patients tolerated chemotherapy well. No recurrence was found during the 9-month follow-up. Lessons Although PSST is an extremely rare disease, we should raise our awareness when we encounter a rapidly growing, cystic-solid mixed thyroid mass with neck compression symptoms to avoid misdiagnosis. Intraoperatively, surgeons should refine surgical procedures to avoid capsular rupture and tumor local implantation metastasis. Intraoperative frozen section pathology is necessary sometimes, especially when the diagnosis could not be established before surgery.